Quest for Quality for Students. Going back to basics. Volume I - ESU (European Students' Union, 2012)
This publication presents the data collected through the first stage of the QUEST project research, which consisted of desk research, a survey among ESU’s members, national site visits and focus group exercise focusing on the barriers towards student participation in quality assurance processes.
Keywords: évaluation de l'enseignement